Evaluation of the anti-malarial activity of crude extract and solvent fractions of the leaves of Olea europaea (Oleaceae) in mice - Desye Misganaw; Ephrem Engidawork; Teshome Nedi (BMC, 2019)
Abstract Background Drug resistance poses a challenge to malaria control measures. This calls for discovery & development of new chemotherapeutic agents. This study therefore was initiated to investigate the antimalarial activity of Olea europaea against Plasmodium berghei infected mice and to further ascertain in which fraction (s) the constituents responsible for anti-malarial activity are concentrated. Methods The leaves of Olea europaea were extracted by maceration using 80% methanol and the crude extract was then successively fractionated with solvents of differing polarity (chloroform, n-butanol and water). The anti-malarial activity of various doses of the extract and fractions (200, 400 and 600 mg/kg) was evaluated using chemo-suppressive, curative, and repository tests. Parameters, including parasitemia, rectal temperature, body weight, and packed cell volume were determined to establish the activity. Results The acute oral toxicity test result revealed that the LD50 values of the extract and fractions were greater than 2000 mg/kg in mice. The crude extract significantly reduced parasitemia (p < 0.001) and prolonged survival time (p < 0.001), in a dose-dependent manner, in all tests, as compared to the negative control group. Higher parasitemia suppression (58%) was achieved with the larger dose (600 mg/kg) in the 4-day suppressive test, suggesting that the crude extract has largely a chemo-suppressive activity. Parasitemia was significantly reduced (p < 0.001) by all fractions in all doses used when compared to the negative controls, with the rank order of n-butanol (51%) > chloroform>aqueous (21%) fractions. Larger (600 mg/kg) and middle (400 mg/kg) doses of the crude extract as well as the fractions ameliorated all the other parameters in a consistent manner, with the crude being more active than the fractions. Preliminary phytochemical analysis revealed the presence of secondary metabolites that were differentially distributed in the fractions. Conclusion The findings collectively indicate that the plant is endowed with antimalarial activity, the activity being more in the crude extract than the fractions, owing to the presence of secondary metabolites that act independently or in synergy. The varying degree of antimalarial activity in the fractions suggests that non-polar and medium polar principles could be responsible for the observed activity.